2017
DOI: 10.1103/physrevd.96.044012
|View full text |Cite
|
Sign up to set email alerts
|

Newtonian potential and geodesic completeness in infinite derivative gravity

Abstract: Recent study has shown that a non-singular oscillating potential -a feature of Infinite Derivative Gravity (IDG) theories -matches current experimental data better than the standard GR potential. In this work we show that this non-singular oscillating potential can be given by a wider class of theories which allows the defocusing of null rays, and therefore geodesic completeness. We consolidate the conditions whereby null geodesic congruences may be made past-complete, via the Raychaudhuri Equation, with the r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…22, for two different values of n For large n, f (r) can be approximated very well by the following functions [62] f (r) = α 1r 0 <r < 1 where α 1 = 0.544, α 2 = 0.572, θ = 0.885π (see also Ref. [115] for a similar parametrization).…”
Section: Iii4 Oscillating Newtonian Potential From Non-local Gravitmentioning
confidence: 90%
“…22, for two different values of n For large n, f (r) can be approximated very well by the following functions [62] f (r) = α 1r 0 <r < 1 where α 1 = 0.544, α 2 = 0.572, θ = 0.885π (see also Ref. [115] for a similar parametrization).…”
Section: Iii4 Oscillating Newtonian Potential From Non-local Gravitmentioning
confidence: 90%
“…Observe, however, the particular shape of the Green functions a bit closer. There appears to be a substructure: whereas the N = 1 Green functions decay like 1/r for large values of the dimensionless radial distance M r, there exist noticeable oscillations in the potentials for the cases N = 2, 3 [3,8,9,10,7]; for a visualization, see Fig. 1.…”
Section: Gravitational Friedel Oscillationsmentioning
confidence: 98%
“…Previous work has shown that IDG gives a non-singular potential for a test mass in a flat background, which returns to the observed GR prediction at large distances [14,24,26]. Even though this calculation was made using the linearised equations of motion, if the test mass is small enough then the perturbation will still be in the linear regime.…”
mentioning
confidence: 71%